Fire performance of ultra-high performance concrete: effect of fine aggregate size and fibers - Zhang, Dong (2022)
This study conducted a thorough investigation on the combined effects of fine aggregate (FA) size, steel fiber, and polypropylene (PP) fiber on the spalling behavior and mechanical properties of ultra-high-performance concrete (UHPC) at high temperature. FAs with 0.6, 2.36, and 4.75 mm were incorporated with steel fibers or PP fibers in UHPC. Test results showed that the synergistic enhancement in spalling prevention of UHPC at high temperature was only found in the combination of PP fiber and large-sized FA. Large-sized FA not only increased the fraction of microcracks but also enhanced their connectivity in UHPC with PP fibers, thus increasing the permeability and improving the spalling resistance at high temperature. This reduced the required PP fiber content for spalling prevention. Besides, steel fibers and large-sized FAs had a combined negative effect on mechanical properties above 600 °C, resulting in even lower mechanical properties at 900 °C compared to UHPC without any fiber and UHPC with PP fibers. Microstructural observation also found that the degradation of steel fibers and microcracks generated by expansion of aggregate both severely damaged the microstructures of UHPC at 900 °C. By contrast, adding PP fibers reduced compressive strength of UHPC below 600 °C due to the voids left by the decomposition of PP fibers, but it did not affect compressive strength at 900 °C, as the cracks in the matrix was enlarged, which reduced the negative effect of PP fibers.